Socioeconomic status and orthodontic treatment need based on the Dental Health Component - Hilda Fitria Lubis; Hilda Paula Laturiuw (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: The dental health component (DHC) is used to assess different malocclusions by evaluating the number of teeth, overjet, overbite and contact points of each tooth. This index is subjectively influenced by socioeconomic factors. Purpose: This study aimed to determine the overview of the socioeconomic status and orthodontic treatment need based on the DHC of State 15 Medan Junior High School students. Methods: This study represented a descriptive research featuring cross-sectional design. The subjects of this study consisted of 100 high school students. This study was conducted by making dental impressions and distributing questionnaires. Data analysis was conducted with SPSS 17.0 software using a descriptive statistical test and presented in a distribution and frequency table. Results: 89% of subjects demonstrated DHC levels of 1-2. 66.3% of subjects with parents of secondary education level had DHC grades 1-2, followed by 31.5% with parents of higher education level and 2.2% with parents of basic education level. The majority of subjects with DHC grades 1-2 had parents occupying class 2 jobs and the lowest number of students had parents holding class 4 jobs. The majority of the subjects with DHC grades 1-2 (77.5%) were of low income parents. Conclusion: The largest distribution of orthodontic treatment need based on DHC among students of State 15 Junior High School occurred at levels 1-2 which either required or did not require minor orthodontic treatment. The majority of the students with DHC grades 1-2 have parents of secondary education level, a class 2 job and a low monthly income.